Multiple Biopsies and Detection of Cervical Cancer Precursors at Colposcopy - Wentzensen, Nicolas (J Clin Oncol, 2015)
PURPOSE: Women with abnormal cervical cancer screening results are referred to colposcopy and biopsy for diagnosis of cervical cancer precursors (high-grade squamous intraepithelial lesions [HSILs]). Colposcopy with a single biopsy can miss identification of HSILs. No systematic study has quantified the improved detection of HSIL by taking multiple lesion-directed biopsies. METHODS: The Biopsy Study was an observational study of 690 women referred to colposcopy after abnormal cervical cancer screening results. Up to four directed biopsies were taken from distinct acetowhite lesions and ranked by colposcopic impression. A nondirected biopsy of a normal-appearing area was added if fewer than four directed biopsies were taken. HSIL identified by any biopsy was the reference standard of disease used to evaluate the incremental yield and sensitivity of multiple biopsies. RESULTS: In the overall population, sensitivities for detecting HSIL increased from 60.6% (95% CI, 54.8% to 66.6%) from a single biopsy to 85.6% (95% CI, 80.3% to 90.2%) after two biopsies and to 95.6% (95% CI, 91.3% to 99.2%) after three biopsies. A significant increase in sensitivity of multiple biopsies was observed in all subgroups. The highest increase in yield of HSIL was observed for women with a high-grade colposcopic impression, HSIL cytology, and human papillomavirus (HPV) type 16 positivity. Only 2% of all HSILs diagnosed in the participants were detected by biopsies of normal-appearing transformation zone. CONCLUSION: Collection of additional lesion-directed biopsies during colposcopy increased detection of histologic HSIL, regardless of patient characteristics. Taking additional biopsies when multiple lesions are present should become the standard practice of colposcopic biopsy.